THE IMPLEMENTATION OF PROJECT-BASED LEARNING IN TEACHING WRITING OF PROCEDURAL TEXT - Vina Aini Salsabila (Universitas Suryakancana, 2018)
This study aims to identify how project-based learning can help develop students’ writing ability in the form of procedural text. The study used a qualitative case study design. The data were collected through classroom observation, students’ writing, and interview which were analyzed qualitatively. The data show that PBL can develop students’ writing ability in which students improve their capacity in the concept of procedural text involving social function, schematic structure, and linguistic features. Key Words: Project-based learning, writing, procedural text